Rapid ultraviolet curing conductive silver paste for LTCC (Low Temperature Co-Fired Ceramic) and preparation method thereof

By using the use of hyperlove polyester acrylate and tablet -shaped silver powder, prepare a kind of condition silver pulp that is quickly solidified in ultraviolet light, solving the problem of long optical curing time, poor conductivity and viscosity in existing technologies. Realize efficient processing and excellent conductive performance.

CN119381051AInactive Publication Date: 2025-01-28ZHEJIANG MOKE LASER INTELLIGENT EQUIP CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411986573.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the photocuring time of conductive silver paste is relatively long, the conductivity is poor, the slurry viscosity is relatively large, and the fluidity is poor, which affects the processing effect.

Method used

The hyperlove polyester acrylic is used as a prefabricated, combined with sliced ​​silver powder and glass powder, and prepared a kind of conductive silver pulp that can be cured in ultraviolet light through a specific proportional complexity and ball mill dispersing technology.

Benefits of technology

The rapid ultraviolet light curing effect is achieved within 5 seconds. The slurry viscosity is low, the powder is dispersed even, easy to process, the silver pulp resistivity is low, and the conductive performance is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses rapid ultraviolet curing conductive silver paste for LTCC (Low Temperature Co-Fired Ceramic) and a preparation method of the rapid ultraviolet curing conductive silver paste. The rapid ultraviolet curing conductive silver paste comprises the following materials in parts by weight: 10-25 parts of prepolymer; 1-5 parts of a plasticizer; 60 to 85 parts of silver powder; 3-8 parts of glass powder; 0.5 to 2 parts of a photoinitiator; wherein the prepolymer is prepared from hyperbranched polyester acrylate. Hyperbranched polyester acrylate is selected as a prepolymer and compounded with other components in a system according to a specific proportion, the prepared silver paste can be rapidly cured at room temperature under ultraviolet light and can be cured within 5 seconds, the viscosity of the paste is low, powder (silver powder and glass powder) is evenly dispersed, printing processing is easy, and the prepared silver paste is low in resistivity and good in conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive polymer materials, and in particular to a fast ultraviolet light-cured conductive silver paste for LTCC and a preparation method thereof. Background Art

[0002] LTCC (Low Temperature Co-fired Ceramic) technology is a multilayer ceramic technology that combines traditional ceramic process technologies such as ceramic powder process, casting process, ceramic sintering process, as well as electronic component manufacturing technologies such as component design and electromagnetic field simulation, drilling, electrode wiring, and lamination. Through the co-firing of multilayer ceramic materials and electrode materials at low temperature (about 900°C), passive devices, integrated passive components, and ceramic substrates with special structures such as microcavities are obtained. LTCC has become a key technology for miniaturization, chip-based, integrated, modular and multifunctional electronic components due to its good dielectric properties, thermal stability, high-frequency characteristics and multi-layer wiring to achieve 3D integration. In this process, printing technology is the key to realizing the manufacture of circuits, conductive lines and electronic components, and conductive paste is one of its core materials. It is used for electrical connection between layers and active / passive components, which has an important impact on the final performance and service life of components.

[0003] Conductive paste is a composite material composed of conductive filler and organic carrier. Among the conductive fillers, silver has the best conductivity among all metal conductors, and its resistivity is about 1.65×10 -8 Ω·m, and the chemical properties of silver are relatively stable. Therefore, developing a LTCC conductive silver paste with low conductive phase, suitable conductive properties and viscosity has good benefits and practical significance.

[0004] The curing method adopted by traditional conductive silver paste is thermal curing, which takes a long time to cure and consumes a lot of energy, reducing the efficiency of industrial production. However, light curing technology has the advantages of being economical, energy-saving, fast curing rate and environmentally friendly. Applying light curing technology to conductive silver paste can not only speed up the curing speed, but also improve the resolution of printed conductors. Therefore, light curing conductive silver paste is one of the most promising silver pastes at present and has become a new direction for the development of conductive silver paste.

[0005] In the prior art, the invention patent with application number 202311593708.8 discloses a method for preparing single-layer / multilayer ceramic-based circuits using LTCC photocurable conductive silver paste, wherein the preparation method of the photocurable conductive silver paste is as follows: weigh 20 to 25 parts of prepolymer, 10 to 20 parts of active monomer, 1 to 3 parts of photoinitiator, 2 to 4 parts of dispersant and 40 to 60 parts of silver powder by mass; mix the weighed 20 to 25 parts of prepolymer, 10 to 20 parts of active monomer and 1 to 3 parts of photoinitiator to obtain a photosensitive system material, then add the weighed 2 to 4 parts of dispersant and 40 to 60 parts of silver powder to the photosensitive system material and disperse them evenly, and finally degasse to obtain a photocurable printing silver paste, develop a photocurable conductive silver paste that can match the raw ceramic sheet, solve the problems of photocurable conductive silver paste cleaning and substrate dissolution and control of sintering shrinkage matching, and can effectively improve the molding efficiency and electrical properties of LTCC electronic devices. However, the light curing time of the above conductive silver paste is 10s to 60s, which is time-consuming.

[0006] The invention patent with application number 202310807864.3 discloses a silver paste for UV-curable flexible circuit boards, a preparation method and an application method, wherein the silver paste for UV-curable flexible circuit boards includes hydroxy acrylate, glycerol ether-modified vinyl silicone oil, flaky silver powder, photoinitiator or hydroxy acrylate, vinyl-terminated silicone oil, flaky silver powder, photoinitiator and coupling agent. In this scheme, by controlling the ratio of vinyl to acrylate, the two are copolymerized during the photocuring process to form a random copolymer, thereby enhancing the impact resistance of the printed circuit, while combining flexibility, bending resistance and high adhesion on flexible substrates. However, the viscosity of the above-mentioned silver paste is <25Kcps, the viscosity is relatively large, the fluidity is poor, and it is not easy to process. Summary of the invention

[0007] In order to solve the problems of long light curing time, poor conductivity, large paste viscosity, poor fluidity and poor processing effect of the conductive paste in the prior art. The present invention provides a fast ultraviolet light curing conductive silver paste for LTCC, which can achieve fast room temperature curing under ultraviolet light, can complete curing within 5 seconds, has low paste viscosity, uniform powder dispersion, is easy to process, and has low silver paste resistivity. In addition, the present invention also provides a preparation method of the above-mentioned fast ultraviolet light curing conductive silver paste for LTCC.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention provides a fast ultraviolet light curing conductive silver paste for LTCC, comprising the following materials in parts by weight: Prepolymer 10-25 parts; 1 to 5 parts of plasticizer; Silver powder 60-85 parts; 3-8 parts of glass powder; Photoinitiator 0.5-2 parts; Wherein, the prepolymer comprises hyperbranched polyester acrylate.

[0009] Using the above technical solution: In the present invention, hyperbranched polyester acrylate is selected as the prepolymer. Hyperbranched polyester acrylate is a type of polymer with a highly branched three-dimensional structure. It contains multiple reactive functional groups, a large number of external active end groups and an internal cavity structure, so that its reaction activity is relatively high, which helps to quickly form a densely cross-linked network and improve the curing speed. Secondly, by using hyperbranched polyester acrylate as a photocurable resin prepolymer, a slurry with a relatively low viscosity can be prepared. The molecular structure of hyperbranched polyester acrylate has a high degree of branching. This branching structure can effectively reduce the entanglement between chains, so that the interaction force between polymer chains is weakened, so that it has a relatively low viscosity. The viscosity at 25°C is 1400cp, and the fluidity is good. The molecular structure of the hyperbranched polyester acrylate gives it good wettability, which enables it to better interact with silver powder and glass powder, effectively disperse the powder, and reduce the increase in viscosity, thereby maintaining the fluidity and low viscosity of the slurry. In addition, the hyperbranched polyester acrylate has good wettability, can effectively disperse silver particles, avoid agglomeration, thereby improving the formation of conductive paths, and the hyperbranched polyester acrylate itself has certain conductive properties, and the hyperbranched structure provides more contact points, which promotes the connection between silver particles, and can form a more effective conductive network together with the silver powder to improve the overall conductivity.

[0010] In the present invention, hyperbranched polyester acrylate is selected as a prepolymer and compounded with other components in the system in a specific ratio. The prepared silver paste can be quickly cured at room temperature under ultraviolet light and can be cured within 5 seconds. The paste has low viscosity, and the powder (silver powder and glass powder) is evenly dispersed, which is easy to print and process. The prepared silver paste has low resistivity and good conductive performance.

[0011] Furthermore, the number average molecular weight of the hyperbranched polyester acrylate is 16000 to 22000. When the hyperbranched polymer is at the above relatively small molecular weight, it helps to further reduce the viscosity of the silver paste.

[0012] Furthermore, the silver powder is flaky silver powder, and the average particle size D50 is 0.2-1 μm.

[0013] Silver powder, as the conductive phase of the conductive paste, determines the conductivity of the silver layer after sintering. At present, the morphology of silver powder used in electronic paste is generally spherical, quasi-spherical, and flake. The particle size of spherical silver powder is generally 1-5μm, and it has good dispersibility and stacking density in the paste, which is conducive to improving the density and good conductivity of the sintered silver layer. However, the conductivity of spherical silver powder in the conductive layer depends on the point contact between particles, with high resistance and poor conductivity. Due to its unique two-dimensional structure, the contact area of ​​flaky silver powder in the silver paste is larger than that of silver powder of other morphologies. The silver paste produced has lower resistance and better conductivity. At the same time, the surface area of ​​flaky silver powder is large, so the silver paste made of flaky silver powder of equal mass has a larger coating area, so that it can maintain good conductivity while reducing the silver content and coating thickness in the silver paste. However, the silver paste prepared by flaky silver powder has poor fluidity, which affects the dispersion of the paste. In order to increase the fluidity of silver paste, flaky silver powder with a smaller particle size is selected in the present application, and the average particle size D50 is 0.2 to 1 μm. However, as the particle size of the flaky silver powder decreases, it is more likely to agglomerate. In the product system of the present application, hyperbranched polyester acrylate is selected as the prepolymer, which reacts with the flaky silver powder with a small particle size to evenly disperse the flaky silver powder with a small particle size in the system, thereby avoiding the agglomeration of the flaky silver powder with a small particle size. While improving the fluidity of the silver paste, a more uniform conductive network is formed with good conductivity. Moreover, the hyperbranched structure provides more contact points, which promotes the connection between the flaky silver powders. The hyperbranched polyester acrylate and the flaky silver powder together form a more effective conductive network, thereby improving the overall conductivity.

[0014] Furthermore, the plasticizer is dibutyl phthalate or diethyl phthalate.

[0015] Dibutyl phthalate and diethyl phthalate molecules insert between hyperbranched polyester acrylate polymer chains, reducing the interaction between polymer chains, thereby reducing the overall viscosity and enhancing flow characteristics. Dibutyl phthalate and diethyl phthalate molecules also help the slurry achieve better adhesion and conductivity, and improve the flexibility, processability and overall performance of the slurry. In addition, it can also improve the mechanical properties of the cured slurry, making it more durable and elastic in application.

[0016] Furthermore, a small amount of one or more of bisphenol A epoxy acrylate, novolac epoxy acrylate, and epoxidized oil acrylate may be added to the prepolymer for compounding.

[0017] Furthermore, the average particle size D50 of the glass powder is 1 to 2 μm.

[0018] Glass powder acts as a bonding phase and sintering aid. In the amorphous state, the glass material has good fluidity and can spread and wet the substrate and silver paste well to obtain a uniform conductive silver paste with good dispersion and moderate viscosity. In addition, the linear expansion coefficients of the ceramic substrate and the silver powder are very different. During co-firing, stress will be generated at the interface of the two materials, causing deformation of the ceramic substrate. By adding the glass phase, the glass powder softens at high temperatures and is in a viscous flow state. It can eliminate stress through its own plastic deformation and reduce the shrinkage of the silver layer, which is beneficial to improving the sintering density of the silver layer and the secondary growth of silver grains, improving the co-firing matching, and effectively ensuring the adhesion and electroplating resistance of the silver layer to the substrate.

[0019] Specifically, the glass powder includes the following components in percentage by mass: 40-70% bismuth oxide, 5-20% boric acid, 5-20% silicon oxide, 5-10% basic copper carbonate, 0.5-2% manganese dioxide, 0-5% alkaline earth metal oxide, 0-3% alkali metal oxide or a mixture of the above, and the particle size D50 is 1-2 μm.

[0020] Furthermore, the photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-methylphenylpropane-1-one, benzoin dimethyl ether, o-benzoylbenzoic acid methyl ether, and benzophenone.

[0021] The second aspect of the present invention provides a method for preparing the above-mentioned fast ultraviolet light curing conductive silver paste for LTCC, comprising the following steps: S1. Weigh the prepolymer, plasticizer, silver powder, glass powder and photoinitiator in the formula; S2, stirring and mixing the prepolymer, the photoinitiator and the plasticizer to obtain a photosensitive material system; S3. Then add the silver powder and glass powder to the photosensitive material system, first use a planetary ball mill to disperse them, and then transfer the slurry to a three-roll grinder to grind and refine the silver paste for multiple times until the fineness of the slurry is less than 10μm to obtain a fast UV-curable conductive silver paste, which is then refrigerated and sealed and stored at 4°C.

[0022] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, hyperbranched polyester acrylate is selected as a prepolymer and compounded with other components in the system in a specific ratio. The prepared silver paste can be quickly cured at room temperature under ultraviolet light and can be cured within 5 seconds. The paste has low viscosity, and the powder (silver powder and glass powder) is evenly dispersed, which is easy to print and process. The prepared silver paste has low resistivity and good conductive performance. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 A fast ultraviolet light curing conductive silver paste for LTCC, comprising the following components: Prepolymer 16 parts; 3 parts of plasticizer; Silver powder 75 parts; 5 parts of glass powder; 1 part of photoinitiator.

[0025] The prepolymer is a hyperbranched polyester acrylate, and the number average molecular weight thereof is 16000-22000.

[0026] The plasticizer is dibutyl phthalate.

[0027] The silver powder is flaky silver powder, and the average particle size D50 is 0.2 to 1 μm.

[0028] The average particle size D50 of the glass powder is 1 to 2 μm.

[0029] The photoinitiator is benzoin dimethyl ether.

[0030] The preparation process of the above-mentioned LTCC fast UV-curing conductive silver paste is as follows: S1. Weigh the prepolymer, plasticizer, silver powder, glass powder and photoinitiator in the formula; S2, adding the prepolymer, photoinitiator and plasticizer into a container, and using a stirrer to fully stir and mix them to obtain a photosensitive material system; S3. Then add silver powder and glass powder to the photosensitive material system, first use a planetary ball mill at a speed of 600 rpm for 4 hours, and then transfer the slurry to a three-roll grinder for multiple grinding to refine the silver paste until the fineness of the slurry is less than 10 μm to obtain a fast UV-curable conductive silver paste, which is refrigerated and sealed and stored at 4°C.

[0031] Example 2 A fast ultraviolet light curing conductive silver paste for LTCC, comprising the following components: Prepolymer 20 parts; 1 part of plasticizer; Silver powder 70 parts; 8 parts of glass powder; 1 part of photoinitiator.

[0032] The prepolymer is a hyperbranched polyester acrylate, and the number average molecular weight thereof is 16000-22000.

[0033] The plasticizer is dibutyl phthalate.

[0034] The silver powder is flaky silver powder, and the average particle size D50 is 0.2 to 1 μm.

[0035] The average particle size D50 of the glass powder is 1 to 2 μm.

[0036] The photoinitiator is benzoin dimethyl ether.

[0037] The preparation process of the fast ultraviolet light curing conductive silver paste for LTCC in this embodiment is the same as that in Example 1.

[0038] Example 3 A fast ultraviolet light curing conductive silver paste for LTCC, comprising the following components: Prepolymer 10 parts; 5 parts of plasticizer; Silver powder 85 parts; 3 parts of glass powder; 2 parts of photoinitiator.

[0039] The prepolymer is a hyperbranched polyester acrylate, and the number average molecular weight thereof is 16000-22000.

[0040] The plasticizer is dibutyl phthalate.

[0041] The silver powder is flaky silver powder, and the average particle size D50 is 0.2 to 1 μm.

[0042] The average particle size D50 of the glass powder is 1 to 2 μm.

[0043] The photoinitiator is benzoin dimethyl ether.

[0044] The preparation process of the fast ultraviolet light curing conductive silver paste for LTCC in this embodiment is the same as that in Example 1.

[0045] Example 4 A fast ultraviolet light curing conductive silver paste for LTCC, comprising the following components: Prepolymer 25 parts; 1 part of plasticizer; Silver powder 75 parts; 4 parts of glass powder; 0.5 parts of photoinitiator.

[0046] The prepolymer is a hyperbranched polyester acrylate, and the number average molecular weight thereof is 16000-22000.

[0047] The plasticizer is dibutyl phthalate.

[0048] The silver powder is flaky silver powder, and the average particle size D50 is 0.2 to 1 μm.

[0049] The average particle size D50 of the glass powder is 1 to 2 μm.

[0050] The photoinitiator is benzoin dimethyl ether.

[0051] The preparation process of the fast ultraviolet light curing conductive silver paste for LTCC in this embodiment is the same as that in Example 1.

[0052] Comparative Example 1 Comparative Example 1 is a comparative test example of Example 1, and the difference between it and Example 1 is that: The prepolymer in Comparative Example 1 is novolac epoxy acrylate, and the remaining components, amounts and preparation process are the same as those in Example 1.

[0053] Comparative Example 2 Comparative Example 2 is a comparative test example of Example 1, and the difference between it and Example 1 is that: The average particle size D50 of the flaky silver powder in Comparative Example 2 is 2-5 μm, and the remaining components, amounts and preparation process are the same as those in Example 1.

[0054] Comparative Example 3 Comparative Example 3 is a comparative test example of Example 1, and the difference between it and Example 1 is that: In Comparative Example 3, no plasticizer was added, and the remaining components, amounts and preparation process were the same as those in Example 1.

[0055] Comparative Example 4 Comparative Example 4 is a comparative test example of Example 1, and the difference between it and Example 1 is that: In Comparative Example 4, no glass powder was added, and the remaining components, amounts and preparation process were the same as those in Example 1.

[0056] The silver pastes prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to pre-curing performance tests, including the viscosity of the silver paste and the volume sedimentation rate after standing for 24 hours. The silver paste viscosity test conditions were as follows: the test equipment model was Brookfield HBT utility cup and spindle (SC4-14 / 6R), the speed was set to 10 rpm / min, the test temperature was 25±1°C, and the test results were shown in Table 1.

[0057] The performance of the silver pastes prepared in Examples 1-4 and Comparative Examples 1-4 was tested after curing. The silver pastes prepared in Examples 1-4 and Comparative Examples 1-4 were printed on PET (polyethylene terephthalate) films using a 300-mesh screen, and then cured at a wavelength of 405 nm and a power density of 10 mW / cm2 The photocuring molding was carried out under the conditions of , and the time required for the silver paste to cure was tested. The cured silver paste was then placed in a 100°C oven and baked for 10 minutes for drying. The resistivity, adhesion and hardness of the dried and cured silver paste were tested.

[0058] Specifically, a four-probe impedance tester was used to test the resistivity of the cured silver paste, the adhesion test was conducted using the GBT 9286-1998 standard, and the hardness test was conducted using the coating pencil hardness test GBT 6739-1996 standard. The test results are shown in Table 1.

[0059] Table 1

[0060] From the test results in Table 1, it can be seen that the silver paste prepared in Examples 1-4 is quickly cured at room temperature under ultraviolet light, has low paste viscosity, low resistivity, good conductivity, and strong adhesion.

[0061] In Comparative Example 1, conventional phenolic epoxy acrylate was used as the prepolymer. Compared with Example 1, the viscosity of the prepared silver paste was greatly improved, the photocuring time was longer, and the resistivity of the silver paste was increased and the adhesion was reduced.

[0062] Compared with Example 1, Comparative Example 2 uses silver powder with a larger particle size, and the resistivity of the silver paste prepared in Comparative Example 2 is significantly increased.

[0063] In Comparative Example 3, since no plasticizer is added, the viscosity of the silver paste increases, and the hardness of the silver paste after final curing is relatively high, which has a significant impact on the subsequent co-firing matching of the conductive silver paste and the LTCC substrate.

[0064] In Comparative Example 4, since no glass powder was added, the adhesion and hardness of the silver paste after curing were significantly reduced.

[0065] After the conductive silver paste in Examples 1-4 was printed, the surface was flat, with no burrs on the edges and no seepage, indicating that it had printing performance; after the conductive silver paste was sintered, there were no obvious holes in the silver layer and no warping deformation at the interface, indicating that the conductive silver paste had good co-firing matching with the LTCC substrate.

[0066] In Comparative Example 1, the surface is uneven, and there are burrs and seepage on the edges, indicating that it does not have printing performance; after the conductive silver paste is sintered, the silver layer has obvious holes and there is severe warping and deformation at the interface, indicating that the conductive silver paste and the LTCC substrate do not have good co-firing matching.

[0067] In Comparative Example 2, the surface is flat, with no burrs or seepage on the edges, indicating that it has printing performance; after the conductive silver paste is sintered, there are no holes in the silver layer and no warping or deformation at the interface, indicating that the conductive silver paste has good co-firing matching with the LTCC substrate.

[0068] In Comparative Example 3, the surface is basically flat, with no burrs on the edges and no seepage, indicating that it has printing performance; after the conductive silver paste is sintered, the silver layer has no holes and there is warping deformation at the interface, indicating that the conductive silver paste and the LTCC substrate do not have good co-firing matching.

[0069] In Comparative Example 4, the surface is flat, with no burrs or seepage on the edges, indicating that it has printing performance; after the conductive silver paste is sintered, there are no obvious holes in the silver layer, and there is obvious warping deformation at the interface, indicating that the conductive silver paste and the LTCC substrate do not have good co-firing matching.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fast ultraviolet light curing conductive silver paste for LTCC, characterized in that: The materials include the following parts by weight: Prepolymer 10-25 parts; 1 to 5 parts of plasticizer; Silver powder 60-85 parts; 3-8 parts of glass powder; Photoinitiator 0.5-2 parts; Wherein, the prepolymer comprises hyperbranched polyester acrylate.

2. The fast ultraviolet curing conductive silver paste for LTCC according to claim 1, characterized in that: The number average molecular weight of the hyperbranched polyester acrylate is 16,000-22,000.

3. The fast UV-curing conductive silver paste for LTCC according to claim 1, characterized in that: The silver powder is flaky silver powder, and the average particle size D50 is 0.2-1 μm.

4. The fast ultraviolet light curing conductive silver paste for LTCC according to claim 1, characterized in that: The plasticizer is dibutyl phthalate or diethyl phthalate.

5. The fast UV-curing conductive silver paste for LTCC according to claim 1, characterized in that: The prepolymer also includes one or more of bisphenol A epoxy acrylate, novolac epoxy acrylate, and epoxidized oil acrylate.

6. The fast ultraviolet light curing conductive silver paste for LTCC according to claim 1, characterized in that: The average particle size D50 of the glass powder is 1 to 2 μm.

7. The fast ultraviolet curing conductive silver paste for LTCC according to claim 1, characterized in that: The photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-methylphenylpropane-1-one, benzoin dimethyl ether, o-benzoylbenzoic acid methyl ether, and benzophenone.

8. A method for preparing a fast ultraviolet curing conductive silver paste for LTCC according to any one of claims 1 to 7, characterized in that: The steps include: S1. Weigh the prepolymer, plasticizer, silver powder, glass powder and photoinitiator in the formula; S2, stirring and mixing the prepolymer, the photoinitiator and the plasticizer to obtain a photosensitive material system; S3. Then, the silver powder and the glass powder are added into the photosensitive material system, and grind and disperse them for multiple times to obtain a refined silver paste.

9. The method for preparing the fast ultraviolet curing conductive silver paste for LTCC according to claim 8, characterized in that: In the step S3, the fineness of the refined silver paste is less than 10 μm.

Citation Information

Patent Citations

  • Silver paste for UV-curable flexible circuit boards, preparation method and application method

    CN116543951B

  • Method for preparing single-layer / multi-layer ceramic-based circuit by LTCC (Low Temperature Co-Fired Ceramic) photocuring conductive silver paste

    CN117500175A

  • Nanowire-based flexible transparent conducting electrode and preparation method thereof

    CN104882190A

  • UV conductive silver paste formula and preparation method thereof

    CN106205775A

  • Liquid metal conductive paste and electronic device

    CN111128441A